2019
DOI: 10.1002/pi.5750
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional poly(ethylene glycol) based crosslinked network polymers as electrolytes for all‐solid‐state lithium ion batteries

Abstract: Polymer electrolyte based lithium ion batteries represent a revolution in the battery community due to their intrinsic enhanced safety, and as a result polymer electrolytes have been proposed as a replacement for conventional liquid electrolytes. Herein, the preparation of a family of crosslinked network polymers as electrolytes via the ‘click‐chemistry’ technique involving thiol‐ene or thiol‐epoxy is reported. These network polymer electrolytes comprise bifunctional poly(ethylene glycol) as the lithium ion so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
0
24
2
Order By: Relevance
“…Another report by Grewal et al also suggests the suitability of using click reactions as a tool for producing crosslinked SPEs. 452 Here, along with thiol-ene chemistry, thiol-epoxy click reaction is also demonstrated as an efficient tool for the SPE preparation (Figure 26c). Although the in situ processing of the LPB cell is not attempted in this work, the thiol-epoxy click chemistry is also expected to gain attention in the near future, which gives enough maneuverability to the production of various types of PEs.…”
Section: In Situ Processing By Direct Deposition Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report by Grewal et al also suggests the suitability of using click reactions as a tool for producing crosslinked SPEs. 452 Here, along with thiol-ene chemistry, thiol-epoxy click reaction is also demonstrated as an efficient tool for the SPE preparation (Figure 26c). Although the in situ processing of the LPB cell is not attempted in this work, the thiol-epoxy click chemistry is also expected to gain attention in the near future, which gives enough maneuverability to the production of various types of PEs.…”
Section: In Situ Processing By Direct Deposition Approachmentioning
confidence: 99%
“…In line with improving the electrode|electrolyte interface in such designs, Wei et al 388 adopted the in situ polymerization process for the preparation of an SPE and cell fabrication by a thiol-ene click reaction. 340,377,452,456,457 For this purpose, they employed materials such as PEGDA oligomer, a multi-functional thiol (pentaerythritol tetra (3-mercaptopropionate), PETMP), DMPA, and LiTFSI salt (Figure 26a). The precursor prepared using the above materials is directly deposited over the LFP cathode and UV-cured to produce a PE integrated composite electrode, followed by LMPB fabrication (Figure 26b).…”
Section: In Situ Processing By Direct Deposition Approachmentioning
confidence: 99%
“…The network's mechanical strength varies with the backbone structure and crosslinking degree. H. Kawakami et al found that linear PEG-based crosslinked network exhibits a much higher stress modulus (6.84 MPa) than PEO (0.55 MPa) with similar molecular mass to the network precursor at ambient temperature [86]. As mentioned, when polysiloxane or polyphosphazene is used as the backbone with the side PEO chain, the network is more flexible than the methacrylate or styrene backbone.…”
Section: Crosslinked Polymermentioning
confidence: 99%
“…In network electrolytes formed by linear PEO chains or corresponding block copolymers without a liquid additive, the ionic conductivity depends on the crosslinking degree and chain length between adjacent junction points [86,87]. Moreover, the ionic conduction mechanism also depends on the mesh size of polymer networks [88].…”
Section: Crosslinked Polymermentioning
confidence: 99%
“…Therefore, the modification of PEO-based SPEs mainly focus on how to reduce the crystallinity of PEO to improve the ionic conductivity. Considerable methods have been adopted, such as adding plasticizers [24] and inorganic additives [31], comb modifying [32], cross-linking [33,34], block copolymerization [35,36] and polymer blending [37]. Embedding nanomaterials into SPEs was firstly reported by Steele and Weston in 1982 [38].…”
Section: Introductionmentioning
confidence: 99%